2016
DOI: 10.1038/srep29900
|View full text |Cite
|
Sign up to set email alerts
|

COMT and prenatal maternal smoking in associations with conduct problems and crime: the Pelotas 1993 birth cohort study

Abstract: Conduct problems in childhood and adolescence are significant precursors of crime and violence in young adulthood. The purpose of the current study is to test the interaction between prenatal maternal smoking and COMT Val158Met in conduct problems and crime in the 1993 Pelotas Birth Cohort Study. Conduct problems were assessed through the parent version of the Strengths and Difficulties Questionnaire at ages 11 and 15 years. A translated version of a confidential self-report questionnaire was used to collect c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 50 publications
0
4
1
Order By: Relevance
“…The findings of the present study nominate a contextual childhood risk factor, poverty, as a better predictor of a criminal conviction than perinatal risk factors. Unlike previous investigations, criminal conviction was not associated with externalizing problems 19 , maternal psychiatric diagnosis 30 , lower family control 15 or child maltreatment 11 . The results were consistent in sensitivity analysis.…”
Section: Discussioncontrasting
confidence: 86%
“…The findings of the present study nominate a contextual childhood risk factor, poverty, as a better predictor of a criminal conviction than perinatal risk factors. Unlike previous investigations, criminal conviction was not associated with externalizing problems 19 , maternal psychiatric diagnosis 30 , lower family control 15 or child maltreatment 11 . The results were consistent in sensitivity analysis.…”
Section: Discussioncontrasting
confidence: 86%
“…Prenatal anxiety has also previously been associated with DNA methylation in cord blood, presumably through stress hormones affecting the regulation of placental barrier genes (Monk et al., ). Of interest, both prenatal maternal smoking and internalizing problems have been associated with child externalizing problems in genetically sensitive designs (Salatino‐Oliveira et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…A study examining the interaction between maternal smoking during pregnancy and Val158Met on aggressive behaviors in adolescents found that while Val158Met alone did not significantly predict aggressive behaviors, youth with the Val/Val genotype and with mothers who smoked during pregnancy exhibited the highest rate of aggressive behaviors [72]. On the other hand, Salatino-Oliveira et al [73] demonstrated that neither Val158Met alone nor in interaction with maternal smoking had significant effects on the conduct scores or crime rate in youth [73], similar to a previous study on youth conduct scores [74].…”
Section: Environmental Factorsmentioning
confidence: 99%